Habitat selection of Southern Right Whales (Eubalaena australis) in the breeding ground Península Valdés - Sueyro, Nicolás; Pennino, Maria Grazia; Crespo, Enrique Alberto; Coscarella, Mariano Alberto
The Southern Right Whale (Eubalaena australis) was object of a commercial exploitation until the mid of the XX century, that brought this species to the brink of extinction. The species was protected globally in 1986 and since this moratorium entered into force, populations throughout the southern hemisphere have been recovering at an 8% annual rate. Even so, in Peninsula Valdés (Argentina) it has been observed that the growth rate is decreasing in recent years from near 7% in 2007 to a 0.06% for 2016. In this breeding ground also changes in distribution and group composition have been reported, with mother and calves remainingclose to the shore and solitary individuals relocating to deeper waters or to other coastal areas outsidePenínsula Valdés. We use SDMs to predict the SRW distribution in the Peninsula Valdés incorporatingenvironmental data and records collected by the CENPAT Marine Mammal Laboratory in four differentperiods: 1999-2000, 2004-2007, 2008-2012 and 2013-2016. Predictions maps were then used to assess ifthere was a shift of the SRW distribution in the Peninsula Valdés trough the time and if it was related topopulation growth. Roughness of the seabed, bathymetry and wave energy were used as potential predictorsfor selection of Southern Right Whales. Bayesian hierarchical spatial model (BHSM) were applied toidentify which environmental variables mostly affect their distribution in northern Patagonia and to predicttheir probability of occurrence in un-sampled locations.Among all the variables combination tested, the selected model included the roughness, wave energy andspatial effect, with bathymetry being highly correlated to roughness and hence was excluded from themodels. The selected model was then used to perform the analysis in each period. Overall, roughness showeda positive relationship with the SWR occurrence, preferring consolidated seabed. The wave energy showed anegative relationship with the SWR occurrence, indicating that whales prefer low wave energy areas.Looking at the magnitude of ...